Need Analysis for Development of a Role Playing Learning Model to Increase Student's Learning Motivation in Social Pathology Course - Ria Rizkia Alvi; Muhammad Jaiz; Said Suhil Achmad; Khairiyah Khadijah; Willasari Arien; Wilson Wilson (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to (1) determine the needs of students regarding learning media that can help students improve learning outcomes and motivation; (2) the implementation of Social Pathology learning. It is research and development that is being done here. The Borg Gall development model—which includes preliminary and development studies, expert validation, model updates, hypothetical models derived from validation results, and model testing—is the one that is employed. According to Borg and Gall, the two primary goals of research and development procedures are product development and feasibility testing. Nevertheless, the scope of this research is restricted to the analytical phase, specifically examining the necessity of developing a role-playing learning model in social pathology courses to enhance the desire of students to learn. The participants in this research were third-semester social pathology students. 37 individuals made up the samples using the non-probability sampling method (saturated sample). A modified Likert scale was utilized to create the needs questionnaire, which had four response options: strongly agree, agree, disagree, and disagree strongly. Students and lecturers need a role-playing model. Students and lecturers in the Community Education Study Program need a role-playing model. This is demonstrated by the percentage that was found while examining the financial requirements of the student responses—90% of which were classified as strongly agreeing. Applying the role-playing learning paradigm can boost students' motivation and enhance their academic performance. This needs analysis can be used as the basis of learning innovations that will be applied to have an impact positive learning, which can improve learning motivation students significantly.